Barriers and Facilitators to Public Transportation Use for Individuals with Intellectual and Developmental Disabilities. (2nd January 2021) - Pfeiffer, Beth; DeRita, Jess; Giacomucci, Emily; Gubler, Jacqueline; Halteman, Taylor; O'Donnell, Erin; Seifried, Gretchen; Pompanio, Amber
Abstract: The purpose of this study was to examine the barriers and facilitators of public transportation use and participation from the perspectives of individuals with Intellectual and Developmental Disabilities (IDD). Twelve individuals between the ages of 23 and 34 completed qualitative phenomenological interviews which were transcribed and analyzed using a constant comparative methodology. A total of 10 barriers and 10 facilitators each were identified, with 4 areas overlapping themes. Transportation was identified as a factor influencing participation in work, school, social/leisure and instrumental activities of daily living.